Influence of Online Health Resources on the Experience of Male Reproductive Health Challenges in Nigeria - Uyi E. OSADOLOR; Emmanuel O. AMOO; Mercy ADEBAYO; Akinyimika O. SOWUNMI (Communications of International Proceedings, 2021)
Globally, male sexual disorders are on the increase, with studies reporting three out of every ten Nigerian men suffering from erectile dysfunction or another sexual challenge. The aim of this study is to examine the experience of reproductive health concern is a significant propellant for the use of online health service in Nigeria. A total of 775 out of 844 men selected from 2 Local Government Areas (LGAs) in Lagos State participated, giving a response rate of 91.8%. Data were obtained by means of a questionnaire and were analysed using both univariate and multivariate analysis. The result shows that all the respondents have access to the internet, although frequency and purpose of internet use varied. The result shows that more than half of the respondents use the internet on a daily basis in both study locations. However, in Lagos Island LGA, the main reason for surfing the net was for health-related information search (34.5%) in contrast to social media use (32%) in Ikeja LGA. Furthermore, the result shows that men who had experienced or are currently experiencing either Erectile dysfunction or HIV/AIDs were more likely to have used online health resources compared to men who had never experienced both. The study concludes that the experience of reproductive health concern is a significant propellant for the use of online health service in Nigeria. Hence, the use of online health resources to communicate with men in relation to their reproductive health must be explored.